The Impact of Plant-Based Diets on Inflammation and Immune Function: A Review - Wilczynska, Aleksandra; Jurczuk, Aleksandra; Romaniuk, Sergiusz; Kaczmarek, Wojciech; Bagiński, Konrad; Depta, Piotr; Bałdyga, Paulina; Marciniak, Kinga (Quality in Sport, 2025)
Background: Chronic low-grade inflammation and immune dysregulation contribute to cardiometabolic, autoimmune and infectious diseases. Dietary patterns, particularly plant-based diets, may influence these processes through metabolic, microbial and nutrient-mediated mechanisms. Aim: To summarise current evidence on how plant-based diets affect systemic inflammation, immune activity, gut microbiota–immune interactions and clinical outcomes in infection and autoimmune disease. Methods: A narrative review of studies from PubMed, Scopus and Google Scholar, including randomised trials, cohorts, cross-sectional analyses, systematic reviews, meta-analyses and mechanistic or microbiome-focused research. Findings were synthesised qualitatively. Results: Healthful plant-based diets are consistently associated with lower CRP, IL-6, TNF-α and other inflammatory markers. Mechanistic studies suggest roles for plant nutrients, microbial short-chain fatty acids and reduced ectopic fat in improving immune regulation. Clinical evidence indicates potential reductions in respiratory infections, asthma exacerbations, COVID-19 severity and some autoimmune conditions. Benefits depend on overall diet quality; processed plant-based diets show limited advantages. Conclusions: Plant-based dietary patterns may beneficially modulate inflammation and support immune function, potentially lowering infection-related and autoimmune risks. Evidence remains limited by heterogeneous definitions and short study duration. Well-designed plant-based diets represent a promising non-pharmacological strategy to improve immune and inflammatory health.